1995
DOI: 10.1007/bf01437433
|View full text |Cite
|
Sign up to set email alerts
|

Photofragmentation of C60

Abstract: Abstract.Photo-ionisation and -fragmentation of C6o by 15 ns excimer laser pulses at 308 nm and 193 nm as well as 0.8 ps laser pulses at 193 nm has been studied with reflectron time-of-flight mass spectrometry. The initial fragmentation process is ejection of C,,, n > 2, as opposed to successive Cz evaporation. Studies of the relative intensities of metastable fragmentation processes compared with direct fragmentation provide new insight into the fragmentation mechanism and provide a thermometer for the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
4

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 25 publications
5
46
4
Order By: Relevance
“…Nevertheless, the main fragmentation channel of the Buckminster fullerene ion is the sequential loss of neutral C 2 molecules [1]. Collision induced fragmentation of C + 60 by photons [2,3], atoms [4], fullerenes [5], surfaces [6] and electrons [7][8][9][10] has been investigated. In this context we have measured absolute cross-sections for electron impact induced fragmentation, fragmentation-ionisation and fragmentation-double-ionisation for the fullerene ions C + 60 , C + 58 and C 2+ 60 .…”
Section: -Introductionmentioning
confidence: 99%
“…Nevertheless, the main fragmentation channel of the Buckminster fullerene ion is the sequential loss of neutral C 2 molecules [1]. Collision induced fragmentation of C + 60 by photons [2,3], atoms [4], fullerenes [5], surfaces [6] and electrons [7][8][9][10] has been investigated. In this context we have measured absolute cross-sections for electron impact induced fragmentation, fragmentation-ionisation and fragmentation-double-ionisation for the fullerene ions C + 60 , C + 58 and C 2+ 60 .…”
Section: -Introductionmentioning
confidence: 99%
“…Although today several experiments have measured these "total (inclusive) fragment ion mass distributions," mostly for fullerene targets, and although the origin of this bimodal distribution is generally thought to be due to these two differing fragmentation mechanisms, knowledge on the details of multifragmentation reaction mechanisms (and its contribution to the bimodal distribution) is very scarce and mostly due to molecular simulations [17,18]. In addition, some coincidence experiments have been carried out (using either highly charged ion projectiles or charged C 60 ion projectiles) where two fragmentation products from C 60 have been identified, thereby providing more information on the fragmentation dynamics [11,[19][20][21][22][23].…”
Section: Event-by-event Analysis Of Collision-induced Cluster-ion Framentioning
confidence: 99%
“…The latter has been inferred indirectly from the U-shaped nature of the fragmentation pattern and other properties of the statistical decay mechanism [9,13,17,18,32], and it was concluded that reactions of type (2) are due to prompt multifragmentation events. The present results shed new light on the nature of this event.…”
Section: Event-by-event Analysis Of Collision-induced Cluster-ion Framentioning
confidence: 99%
“…Excited fullerenes exhibit a rich spectrum of unimolecular decay modes: loss of C 2 or larger fragments [1][2][3][4], of electrons [5][6][7][8][9], and emission of photons (infrared and blackbody-like radiation) [10][11][12][13]. Each of these processes has been thoroughly investigated by a number of groups, none of them is quantitatively understood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the competition between them is still unknown. Is it really true that the distribution of even-sized photofragment ions (n ≥ 32) is independent of laser fluence, for multiphoton excitation in the UV [4]? This would support the notion that emission of C 4 or even larger fragments is a significant feeding channel in the amazingly efficient production of even-sized fragment ions below C + 58 .…”
Section: Introductionmentioning
confidence: 99%